On a mechanism that improves efficiency and reduces inequality in voluntary contribution games - Rodney E. Falvey; Tom Lane; Shravan Luckraz (The University of Nottingham, Centre for Decision Research and Experimental Economics (CeDEx), 2022)
We consider the class of linear voluntary contribution games under the general assumption of heterogeneous endowments. In this context, we assess the performance of the Galbraith Mechanism (GM) relative to a fixed equal sharing allocation in both theory and experiments. Three main empirical results emerge. First, the GM raises average contributions significantly above those under an equal-shares allocation. Second, the GM simultaneously reduces income inequality as it improves efficiency. Third, a player's contribution and allocation behaviour is sensitive to her position in the endowment distribution. In all their decision-making, agents consistently place greater emphasis on contribution levels when they are rich, and on contribution ratios (contributions relative to endowments) when they are poor.
Keywords: 330